“The First Armenian National Classical Opera is 155 Years Old” - Ghazaryan Դավիթ Գարսեվանի (Musical Armenia, 2024)
The author of the article touched upon the 155th anniversary of Tigran Chukhajyan’s First Armenian National Classical Opera Arshak II, created in 1868. The article is written in a very relevant way emphasizing the place and role of opera from the point of view of today with the comments it gives. The author of the article addresses both the composer’s life, especially his studies and education, as well as the Armenian center and the European cultural environment, which laid the foundations for the foundation of the National Opera. He created not only opera, but also stage and instrumental music, genres that have passed the composer’s curation of singing. The author of the article emphasizes the importance of the existence of the opera professional composer school "Arshak II", which has existed for half a century.